2020
DOI: 10.3390/jcm9041189
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Penile Cuff Test and Conventional Urodynamic Study Prior to Photoselective Vaporization of Prostate for Benign Prostate Hyperplasia Using a 120 W GreenLight High Performance System Laser

Abstract: Background: We compared the utility of the penile cuff test (PCT) and the conventional urodynamic study (UDS) for the preoperative assessment of patients undergoing scheduled photoselective vaporization of the prostate (PVP) for benign prostate hyperplasia (BPH). Methods: Fifty-nine patients with voiding lower urinary tract symptoms (LUTS) underwent a simultaneous PCT and conventional UDS before PVP. The modified International Continence Society (ICS) nomogram was used to confirm bladder outlet obstruction aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“… 34 37 50 One study evaluated a similar compression index as beforementioned and found a moderate sensitivity (78%) and good specificity (84%) at an index cut-off value of 160% to predict BOO. 34 The sensitivity for the measured maximum urinary flow with the penile cuff to predict BOO was good (80% 37 and 100% 50 ) with a fair to good specificity of (56% 50 and 100% 37 ).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“… 34 37 50 One study evaluated a similar compression index as beforementioned and found a moderate sensitivity (78%) and good specificity (84%) at an index cut-off value of 160% to predict BOO. 34 The sensitivity for the measured maximum urinary flow with the penile cuff to predict BOO was good (80% 37 and 100% 50 ) with a fair to good specificity of (56% 50 and 100% 37 ).…”
Section: Resultsmentioning
confidence: 95%
“…Then, full-text screening was performed for 152 studies, of which 61 studies met all selection criteria and were scored using the COSMIN checklist. Subsequently, 37 studies received a COSMIN score of fair, good or excellent 21–57. Twenty-four studies58–81 received ‘poor’ COSMIN scores and were therefore excluded from the best evidence synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations